Hydrophilic self-cleaning archaized brick and preparation method thereof

By using a hydrophilic self-cleaning glaze layer with high surface tension in antique bricks, combined with reducing atmosphere and homogenization of glaze, the problem of insufficient aging resistance and binding strength of hydrophilic self-cleaning coatings in the prior art is solved. , achieves lasting self-cleaning performance and reduces production costs.

CN119118511AActive Publication Date: 2024-12-13FOSHAN DONGPENG CERAMIC +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411258364.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The hydrophilic self-cleaning coatings of existing antique bricks have poor aging resistance and limited binding power, resulting in poor self-cleaning aging and unable to meet actual use needs. At the same time, the additional coating of hydrophilic self-cleaning coatings is not conducive to reducing production costs.

Method used

Using a hydrophilic self-cleaning antique brick preparation method, hydrophilic fuses containing lithium carbonate, calcined talc, zinc oxide, aluminum trioxide, quartz and silicon carbide, hydrophilic self-cleaning glaze of kaolin and silicon carbide The material is calcined to form an enamel layer with high surface tension, and combined with a reducing atmosphere to promote homogenization and adhesion of the glaze layer, achieving long-lasting self-cleaning properties.

Benefits of technology

It improves the aging resistance and bonding of hydrophilic self-cleaning antique bricks, achieves long-lasting self-cleaning performance, reduces production costs, and avoids the need for additional coating of hydrophilic self-cleaning paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034768800000101
    Figure BDA0005034768800000101
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrophilic self-cleaning archaized brick. The preparation method comprises the following steps: A, preparing a hydrophilic frit; wherein the hydrophilic frit is prepared from the following raw materials in percentage by mass: 8 to 12 percent of lithium carbonate, 30 to 50 percent of calcined talc, 4 to 8 percent of zinc oxide, 25 to 35 percent of aluminum oxide, 6 to 12 percent of quartz and 3 to 7 percent of silicon carbide; b, preparing hydrophilic self-cleaning glaze; wherein the hydrophilic self-cleaning glaze is prepared from the following raw materials in percentage by mass: 85 to 95 percent of hydrophilic frit, 4 to 12 percent of kaolin and 1 to 3 percent of silicon carbide; and C, applying the hydrophilic self-cleaning glaze to the green body with the concave-convex effect, drying and calcining to obtain the hydrophilic self-cleaning archaized brick. The preparation method of the hydrophilic self-cleaning archaized brick, provided by the invention, is simple and high in operability, and the obtained hydrophilic self-cleaning archaized brick not only has excellent and lasting self-cleaning property, but also is beneficial to reducing the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building ceramics, in particular to a hydrophilic self-cleaning antique brick and a preparation method thereof. Background Art

[0002] Antique tiles, as an artistic building material that combines classical aesthetics with modern craftsmanship, are deeply favored by consumers for their unique antique glaze effect, rich color layers and strong historical charm. They are widely used in home decoration, commercial places, cultural and tourist attractions and other fields.

[0003] In order to ensure the antique effect of antique tiles, the surface of antique tiles is usually designed to be uneven. Although the uneven surface of antique tiles is conducive to increasing their anti-slip performance, it is also easy to become a breeding ground for dirt and grime, which not only affects the aesthetics of antique tiles and reduces their decorative effect, but also makes the dirt treatment of antique tiles time-consuming and laborious, and requires the help of cleaning agents to effectively remove dirt.

[0004] In order to overcome the above-mentioned defects, the prior art usually coats the surface of the antique brick with a hydrophilic self-cleaning coating, so that a layer of hydrophilic self-cleaning coating is formed on the surface of the antique brick, so that water can spread quickly when it contacts the coating surface (i.e., the static contact angle between water and the coating is small) and form a uniform water film, which can penetrate into the interface between the dirt and the coating, thereby weakening the adhesion of the dirt, and under the action of gravity, the continuously flowing water film can take away and remove the dirt on the surface of the antique brick, achieving the effect of self-cleaning. However, due to the poor aging resistance of the hydrophilic self-cleaning coating and its limited bonding force with the brick surface, the hydrophilic self-cleaning coating is easy to fall off, the service life is extremely limited, and the self-cleaning durability is poor, which cannot meet the actual use requirements. At the same time, additionally coating the surface of the antique brick substrate with a hydrophilic self-cleaning coating is not conducive to reducing production costs. Summary of the invention

[0005] The first purpose of the present invention is to provide a method for preparing a hydrophilic self-cleaning antique tile. The preparation method is simple and easy to operate. The obtained hydrophilic self-cleaning antique tile not only has excellent and lasting self-cleaning property, but also helps to reduce costs.

[0006] The second object of the present invention is to provide a hydrophilic self-cleaning antique tile prepared by the above-mentioned preparation method of the hydrophilic self-cleaning antique tile, which has excellent and lasting self-cleaning performance.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A method for preparing a hydrophilic self-cleaning antique tile comprises the following steps:

[0009] A. Prepare a hydrophilic frit; wherein, calculated by mass percentage, the hydrophilic frit comprises the following raw materials: 8-12% lithium carbonate, 30-50% calcined talc, 4-8% zinc oxide, 25-35% aluminum oxide, 6-12% quartz and 3-7% silicon carbide;

[0010] B. Prepare a hydrophilic self-cleaning glaze; wherein, calculated by weight percentage, the hydrophilic self-cleaning glaze comprises the following raw materials: 85-95% of hydrophilic frit, 4-12% of kaolin and 1-3% of silicon carbide;

[0011] C. Applying the hydrophilic self-cleaning glaze to the body with the concave-convex effect, drying and calcining to obtain the hydrophilic self-cleaning antique brick.

[0012] Furthermore, in step A and step B, the particle size of the silicon carbide is ≤2 μm;

[0013] In step A, the particle size of the aluminum oxide is ≤2 μm.

[0014] Furthermore, in step A, the preparation step of the hydrophilic frit is specifically as follows: uniformly mixing the raw materials of the hydrophilic frit according to a ratio, calcining and then quenching with water to obtain the hydrophilic frit;

[0015] The calcination curve of the hydrophilic frit is: heating from room temperature to 1530° C. at a heating rate of 8 to 10° C. / min, and then keeping the temperature for 35 to 45 minutes.

[0016] Furthermore, in step A, the hydrophilic frit includes the following raw materials, calculated by mass percentage: 10% lithium carbonate, 40% calcined talc, 5% zinc oxide, 30% aluminum oxide, 9% quartz and 6% silicon carbide.

[0017] Furthermore, in step B, the specific gravity of the hydrophilic self-cleaning glaze is 1.25 to 1.45.

[0018] Furthermore, in step B, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.2-0.4% by mass.

[0019] Furthermore, in step B, the preparation step of the hydrophilic self-cleaning glaze is: after the raw materials of the hydrophilic self-cleaning glaze are uniformly mixed according to the ratio, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and the hydrophilic self-cleaning glaze is obtained by sieving.

[0020] Furthermore, in step C, the glazing thickness of the hydrophilic self-cleaning glaze is 0.05 to 0.1 mm.

[0021] Furthermore, in step C, the calcination temperature is 1200-1220°C.

[0022] A hydrophilic self-cleaning antique brick is prepared using the above-mentioned method for preparing the hydrophilic self-cleaning antique brick.

[0023] The technical solution provided by the present invention may include the following beneficial effects:

[0024] 1. During the calcination process, silicon carbide decomposes into silicon and carbon monoxide. Carbon monoxide will seize oxygen from the external environment, making the calcination atmosphere a reducing atmosphere. Under a reducing atmosphere, the melt produced by calcination will shrink, causing the new melt produced during the calcination process to continuously roll and float upward, which is beneficial to increase the surface tension. At the same time, the raw materials in the hydrophilic self-cleaning glaze will gradually decompose during the calcination process, causing the hydrophilic self-cleaning glaze to eventually form a glaze melt (i.e., glaze layer) with lithium oxide, silicon oxide, aluminum oxide, magnesium oxide and zinc oxide as the main components. Based on the reducing atmosphere and the large surface tension of each component in the glaze layer, the above two aspects cooperate with each other to make the surface tension of the glaze layer far greater than the surface tension of water, making the glaze layer essentially a hydrophilic self-cleaning glaze layer with extremely strong hydrophilic properties, so that even if there is dirt adhering to the surface of the glaze layer, the dirt is relatively easy to remove.

[0025] 2. Compared with the hydrophilic self-cleaning coating, the aging resistance of the hydrophilic self-cleaning glaze layer is greatly improved, which is conducive to overcoming the technical defects of the prior art that the self-cleaning timeliness is poor due to the poor aging resistance of the hydrophilic self-cleaning coating. In addition, since the hydrophilic self-cleaning glaze layer is directly calcined by the hydrophilic self-cleaning glaze, it has a very high bonding force with the antique brick, which is conducive to overcoming the technical defects of the prior art that the hydrophilic self-cleaning coating has a limited bonding force with the brick surface of the antique brick, resulting in poor self-cleaning timeliness. The mutual coordination of the above-mentioned multiple factors is conducive to achieving the long-lasting self-cleaning of the antique brick, and the self-cleaning is excellent. In addition, the technical solution does not need to additionally coat the surface of the antique brick with a hydrophilic self-cleaning coating, which is conducive to saving production costs and improving production efficiency. DETAILED DESCRIPTION

[0026] The present technical solution provides a method for preparing a hydrophilic self-cleaning antique tile, comprising the following steps:

[0027] A. Prepare a hydrophilic frit; wherein, calculated by mass percentage, the hydrophilic frit comprises the following raw materials: 8-12% lithium carbonate, 30-50% calcined talc, 4-8% zinc oxide, 25-35% aluminum oxide, 6-12% quartz and 3-7% silicon carbide;

[0028] B. Prepare a hydrophilic self-cleaning glaze; wherein, calculated by weight percentage, the hydrophilic self-cleaning glaze comprises the following raw materials: 85-95% of hydrophilic frit, 4-12% of kaolin and 1-3% of silicon carbide;

[0029] C. Applying the hydrophilic self-cleaning glaze to the body with the concave-convex effect, drying and calcining to obtain the hydrophilic self-cleaning antique brick.

[0030] The prior art usually applies a hydrophilic self-cleaning coating on the surface of the antique brick substrate, so that a layer of hydrophilic self-cleaning coating is formed on the surface of the antique brick, so that even if there is dirt on the surface of the antique brick, the dirt can be easily removed. However, due to the poor aging resistance of the hydrophilic self-cleaning coating and its limited bonding with the brick surface, the hydrophilic self-cleaning coating is easy to fall off, the service life is extremely limited, and the hydrophilic self-cleaning durability is poor, which cannot meet the actual use requirements. At the same time, additionally applying a hydrophilic self-cleaning coating on the surface of the antique brick substrate is not conducive to reducing production costs.

[0031] In order to achieve lasting self-cleaning properties while reducing costs, the technical solution proposes a hydrophilic self-cleaning glaze, the raw materials of which include hydrophilic frit, kaolin and silicon carbide, and the raw materials of the hydrophilic frit include lithium carbonate, calcined talc, zinc oxide, aluminum oxide, quartz and silicon carbide. During the calcination process, silicon carbide decomposes into silicon and carbon monoxide, and carbon monoxide will capture oxygen from the external environment, making the calcination atmosphere a reducing atmosphere. Under a reducing atmosphere, the melt produced by calcination will shrink, causing the new melt produced during the calcination process to continuously roll and float upward, which is beneficial to increase the surface tension. At the same time, the raw materials in the hydrophilic self-cleaning glaze will gradually decompose during the calcination process, so that the hydrophilic self-cleaning glaze will eventually form a glaze melt (i.e., a glaze layer) with lithium oxide, silicon oxide, aluminum oxide, magnesium oxide and zinc oxide as the main components; and the surface tension of lithium oxide is 450×10 -3 N / M, the surface tension of silicon oxide is 290×10 -3 N / M, the surface tension of aluminum oxide is 380×10 -3 N / M, the surface tension of magnesium oxide is 545×10 -3 N / M, the surface tension of zinc oxide is 470×10 -3 N / M, while the surface tension of water is 73×10 -3 N / m, that is, the surface tension of each element in the glaze layer is much greater than the surface tension of water. Therefore, based on the reducing atmosphere and the large surface tension of each component in the glaze layer, the above two aspects cooperate with each other to make the surface tension of the glaze layer much greater than the surface tension of water, making the glaze layer essentially a hydrophilic self-cleaning glaze layer with extremely strong hydrophilic properties, so that even if there is dirt on the surface of the glaze layer, the dirt can be removed more easily.

[0032] At the same time, compared with the hydrophilic self-cleaning coating, the aging resistance of the hydrophilic self-cleaning glaze layer is greatly improved, which is conducive to overcoming the technical defects of poor self-cleaning timeliness due to the poor aging resistance of the hydrophilic self-cleaning coating in the prior art. In addition, since the hydrophilic self-cleaning glaze layer is directly calcined by the hydrophilic self-cleaning glaze, its bonding force with the antique brick is extremely high, which is conducive to overcoming the technical defects of poor self-cleaning timeliness due to the limited bonding force between the hydrophilic self-cleaning coating and the brick surface of the antique brick in the prior art. The mutual coordination of the above multiple factors is conducive to achieving the long-lasting self-cleaning of the antique brick, and the self-cleaning is excellent. In addition, the technical solution does not need to additionally coat the surface of the antique brick with a hydrophilic self-cleaning coating, which is conducive to saving production costs and improving production efficiency.

[0033] In addition, the existing common glazes generally generate solid phases and liquid phases during the calcination process, and the solid phase is dispersed and unevenly distributed between the liquid phases, that is, the dispersion uniformity of the glaze melt generated by the existing glazes during the calcination process is poor, so that even if the glaze itself has self-cleaning properties, the uniformity of its self-cleaning properties is poor, and it is impossible to achieve good self-cleaning properties. In the present technical solution, under a reducing atmosphere, the melt generated by calcination will shrink, so that the new melt generated during the calcination process will continue to roll and float upward, which is conducive to homogenizing the melt obtained by calcination. That is, based on the characteristics of silicon carbide, it is conducive to homogenizing the hydrophilic frit and hydrophilic self-cleaning glaze with added silicon carbide, so that the uniformity of the melt obtained by calcination is extremely high. Therefore, the distribution uniformity of the various components in the glaze layer obtained by calcining the hydrophilic self-cleaning glaze obtained in the present technical scheme is relatively high, overcoming the technical defect in the prior art that even if the glaze itself has self-cleaning properties, the distribution uniformity of its self-cleaning properties is poor and better self-cleaning properties cannot be achieved, thereby achieving uniform and lasting self-cleaning properties.

[0034] Further, in step A and step B, the particle size of the silicon carbide is ≤2 μm;

[0035] In step A, the particle size of the aluminum oxide is ≤2 μm.

[0036] In a preferred embodiment of the present technical solution, by adding silicon carbide with a preferred particle size of ≤2 μm into the formula, it is helpful to promote the decomposition of silicon carbide, so that the calcining atmosphere of the glaze is always a reducing atmosphere, thereby ensuring the self-cleaning performance of the glaze.

[0037] Furthermore, by adding aluminum oxide with a particle size of preferably ≤2 μm to the formula, it is helpful to accelerate its melting, thereby promoting the homogenization of the glaze calcination process and ensuring its performance.

[0038] Further, in step A, the preparation step of the hydrophilic frit is specifically as follows: uniformly mixing the raw materials of the hydrophilic frit according to a ratio, calcining and then quenching with water to obtain the hydrophilic frit;

[0039] The calcination curve of the hydrophilic frit is: heating from room temperature to 1530° C. at a heating rate of 8 to 10° C. / min, and then keeping the temperature for 35 to 45 minutes.

[0040] In a preferred embodiment of the present technical solution, the calcination curve of the hydrophilic frit is optimized so that all the raw materials in the hydrophilic frit formula can be melted, which is conducive to promoting phase separation, ensuring the performance of the hydrophilic frit, and making the hydrophilic self-cleaning glaze with the addition of the hydrophilic frit have a certain sense of transparency after calcination, thereby improving its permeability.

[0041] Further, in step A, the hydrophilic frit includes the following raw materials, calculated by mass percentage: 10% lithium carbonate, 40% calcined talc, 5% zinc oxide, 30% aluminum oxide, 9% quartz and 6% silicon carbide.

[0042] In a preferred embodiment of the present technical solution, by limiting the addition amount of each raw material in the hydrophilic frit, it is helpful to optimize the performance of the hydrophilic frit, thereby helping to ensure the performance of the hydrophilic self-cleaning glaze.

[0043] Further description, in step B, the specific gravity of the hydrophilic self-cleaning glaze is 1.25-1.45.

[0044] When the specific gravity of the hydrophilic self-cleaning glaze is too high, the glaze will be too thick and the fluidity will deteriorate, which will make the application uniformity of the hydrophilic self-cleaning glaze poor and easily form defects such as glaze roads. In addition, the high specific gravity of the hydrophilic self-cleaning glaze will easily hinder the discharge of gas and water generated by the hydrophilic self-cleaning glaze during the calcination process, causing the glaze layer obtained by calcining the hydrophilic self-cleaning glaze to crack easily. When the specific gravity of the hydrophilic self-cleaning glaze is too low, the fluidity of the hydrophilic self-cleaning glaze is too good, and it is easy to flow during the glazing process, which also causes the application uniformity of the hydrophilic self-cleaning glaze to be poor, and it is easy to form defects such as glaze roads. In addition, the specific gravity of the hydrophilic self-cleaning glaze is too low, resulting in excessive water in the glaze, and the phenomenon of brick explosion is easy to occur during the calcination process. It should be noted that the glaze road refers to the glaze layer being thicker in some areas and thinner or missing in other areas.

[0045] Further, in step B, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.2-0.4% by mass.

[0046] In a preferred embodiment of the present technical solution, by limiting the fineness of the hydrophilic self-cleaning glaze, the sieve residue of the hydrophilic self-cleaning glaze is relatively low, which is beneficial for making the hydrophilic self-cleaning glaze have fine uniformity, reducing the rough glaze surface caused by uneven particles, and improving the self-cleaning performance.

[0047] Further, in step B, the preparation step of the hydrophilic self-cleaning glaze is: after the raw materials of the hydrophilic self-cleaning glaze are uniformly mixed according to the ratio, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and the hydrophilic self-cleaning glaze is obtained by sieving.

[0048] The technical scheme also proposes a preparation method for a hydrophilic self-cleaning glaze, which is simple and easy to operate. Specifically, calculated by the mass percentage of the dry material of the hydrophilic self-cleaning glaze, the amount of sodium carboxymethyl cellulose added is 0.2%, the amount of sodium tripolyphosphate added is 0.3%, and the amount of water added is 35-38%. After the above additives are added to the mixed material, the mixture is ball-milled for 12 hours and then sieved to obtain the hydrophilic self-cleaning glaze.

[0049] Further, in step C, the glazing thickness of the hydrophilic self-cleaning glaze is 0.05-0.1 mm.

[0050] When the glaze is applied too thick, it is easy to affect the homogenization of the glaze, which in turn leads to a decrease in the self-cleaning performance of the glaze layer obtained by calcining the glaze. When the glaze is applied too thin, it may leak through the body, which also leads to a decrease in the self-cleaning performance of the glaze layer obtained by calcining the glaze.

[0051] Further, in step C, the calcination temperature is 1200-1220°C.

[0052] In a preferred embodiment of the present technical solution, by limiting the glaze firing temperature to 1200-1220°C, which is consistent with the firing temperature of existing antique tile products, it is easy to achieve the purpose of industrialized production while ensuring product performance and reducing large deviations between the experimental stage and the industrialization stage.

[0053] A hydrophilic self-cleaning antique brick is prepared using the above-mentioned method for preparing the hydrophilic self-cleaning antique brick.

[0054] A hydrophilic self-cleaning antique tile prepared by the preparation method of the hydrophilic self-cleaning antique tile has excellent and lasting self-cleaning performance.

[0055] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0056] Performance Testing

[0057] Static contact angle before immersion: According to the test method of GB / T 30447-2013 Nanofilm Contact Angle Measurement Method, the static contact angle of the hydrophilic self-cleaning antique tile before immersion in boiling water is tested. If the static contact angle is <10°, it is qualified.

[0058] Static contact angle after immersion: According to the test method of "GB / T 30447-2013 Nanofilm Contact Angle Measurement Method", the hydrophilic self-cleaning antique tiles are tested for their static contact angle after being immersed in boiling water for 30 days. If the contact angle is less than 25°, it is qualified.

[0059] Anti-slip performance: Anti-slip performance is tested according to the DIN 51130:2014 anti-slip standard.

[0060] Mohs hardness: The Mohs hardness of the hydrophilic self-cleaning antique tile is tested using a Mohs hardness tester.

[0061] Example 1

[0062] A. Calculated by mass percentage, 10% lithium carbonate, 40% calcined talc, 5% zinc oxide, 30% aluminum oxide with a particle size of 1.5 μm, 9% quartz and 6% silicon carbide with a particle size of 1.5 μm are mixed evenly, calcined and then water quenched to obtain a hydrophilic frit; wherein the calcination curve of the hydrophilic frit is: from room temperature to 1530°C at a heating rate of 8-10°C / min, and kept warm for 35 minutes;

[0063] B. Calculated by mass percentage, 90% of hydrophilic frit, 8% of kaolin and 2% of silicon carbide with a particle size of 1.5 μm are uniformly mixed, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and sieved to obtain a hydrophilic self-cleaning glaze with a specific gravity of 1.35; wherein, by mass percentage, the sieve residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.3%; calculated by mass percentage of the dry material of the hydrophilic self-cleaning glaze, the addition amount of sodium carboxymethyl cellulose is 0.2%, the addition amount of sodium tripolyphosphate is 0.3%, and the addition amount of water is 38%;

[0064] C. Applying a hydrophilic self-cleaning glaze to a body with a concave-convex effect, drying and calcining at a temperature of 1200-1220° C. to obtain a hydrophilic self-cleaning antique tile; wherein the glazing thickness of the hydrophilic self-cleaning glaze is 0.08 mm.

[0065] Example 2

[0066] A. 8% lithium carbonate, 32% calcined talc, 6% zinc oxide, 35% aluminum oxide with a particle size of 1.5 μm, 12% quartz and 7% silicon carbide with a particle size of 1.5 μm were mixed evenly according to mass percentage, calcined and water quenched to obtain a hydrophilic frit; wherein the calcination curve of the hydrophilic frit is: from room temperature to 1530°C at a heating rate of 8-10°C / min, and kept warm for 45 minutes;

[0067] B. Calculated by mass percentage, 85% of hydrophilic frit, 12% of kaolin and 3% of silicon carbide with a particle size of 1.5 μm are uniformly mixed, and then sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and sieved to obtain a hydrophilic self-cleaning glaze with a specific gravity of 1.25; wherein, by mass percentage, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.2%; calculated by mass percentage of the dry material of the hydrophilic self-cleaning glaze, the addition amount of sodium carboxymethyl cellulose is 0.2%, the addition amount of sodium tripolyphosphate is 0.3%, and the addition amount of water is 35%;

[0068] C. Applying a hydrophilic self-cleaning glaze to a body with a concave-convex effect, drying and calcining at a temperature of 1200-1220° C. to obtain a hydrophilic self-cleaning antique tile; wherein the glazing thickness of the hydrophilic self-cleaning glaze is 0.05 mm.

[0069] Example 3

[0070] A. 12% of lithium carbonate, 50% of calcined talc, 4% of zinc oxide, 25% of aluminum oxide with a particle size of 1.5 μm, 6% of quartz and 3% of silicon carbide with a particle size of 1.5 μm were mixed uniformly according to mass percentage, calcined and water quenched to obtain a hydrophilic frit; wherein the calcination curve of the hydrophilic frit is: from room temperature to 1530°C at a heating rate of 8-10°C / min, and kept warm for 40 minutes;

[0071] B. Calculated by mass percentage, 93% of hydrophilic frit, 6% of kaolin and 1% of silicon carbide with a particle size of 1.5 μm are uniformly mixed, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and sieved to obtain a hydrophilic self-cleaning glaze with a specific gravity of 1.45; wherein, by mass percentage, the sieve residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.4%; calculated by mass percentage of the dry material of the hydrophilic self-cleaning glaze, the addition amount of sodium carboxymethyl cellulose is 0.2%, the addition amount of sodium tripolyphosphate is 0.3%, and the addition amount of water is 37%;

[0072] C. Applying a hydrophilic self-cleaning glaze to a body with a concave-convex effect, drying and calcining at a temperature of 1200-1220° C. to obtain a hydrophilic self-cleaning antique tile; wherein the glazing thickness of the hydrophilic self-cleaning glaze is 0.1 mm.

[0073] Comparative Example 1

[0074] The hydrophilic self-cleaning antique brick in Comparative Example 1 includes an antique brick substrate and a hydrophilic self-cleaning coating distributed from bottom to top; wherein the hydrophilic self-cleaning coating is obtained by curing a super hydrophilic coating of model SM-TM-QS3500 / 3200 produced by Shangmeng Technology Wuxi Co., Ltd.

[0075] Comparative Example 2

[0076] Comparative Example 2 has the same preparation method and raw materials as Example 1, except that silicon carbide is not added to the hydrophilic frit formula in Comparative Example 2. That is, in Comparative Example 2, the hydrophilic frit includes the following raw materials calculated by mass percentage: 12% lithium carbonate, 40% calcined talc, 5% zinc oxide, 32% aluminum oxide and 11% quartz.

[0077] Comparative Example 3

[0078] Comparative Example 3 has the same preparation method and raw materials as Example 1, except that silicon carbide is not added to the hydrophilic self-cleaning glaze in Comparative Example 3. That is, in Comparative Example 3, the hydrophilic self-cleaning glaze includes the following raw materials calculated by mass percentage: 95% hydrophilic frit and 5% kaolin.

[0079] The performance tests were conducted on the hydrophilic self-cleaning antique tiles prepared by the preparation methods of Examples 1-3 and Comparative Examples 1-3, respectively. The results are shown in Table 1 below:

[0080] Table 1 Performance test results of different hydrophilic self-cleaning antique tiles in the embodiments and comparative examples

[0081]

[0082] It can be seen from the performance test results in Table 1 that the static contact angle of the antique bricks obtained by the present technical solution before immersion is 5-10°, and the static contact angle after immersion is 9-17°. It not only has excellent and lasting self-cleaning performance, but also has good anti-slip properties and hardness, and is both decorative and practical, which is more conducive to meeting the use needs of consumers.

[0083] In Comparative Example 1, a hydrophilic self-cleaning coating is provided on the surface of the antique brick substrate to obtain a hydrophilic self-cleaning antique brick. Although the obtained antique brick has a small static contact angle with water before immersion and has good self-cleaning property, it is affected by the poor aging resistance of the hydrophilic self-cleaning coating and its limited bonding force with the brick surface. As a result, after immersion, the hydrophilic self-cleaning coating of the hydrophilic self-cleaning antique brick in Comparative Example 1 falls off, the hydrophilic self-cleaning durability is poor, and the static contact angle after immersion cannot be measured.

[0084] In Comparative Example 2, since silicon carbide was not added to the hydrophilic frit formula, and in Comparative Example 3, since silicon carbide was not added to the hydrophilic self-cleaning glaze formula, the self-cleaning property of the obtained antique tiles was reduced.

[0085] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a hydrophilic self-cleaning antique tile, characterized in that: The following steps are involved: A. Prepare a hydrophilic frit; wherein, calculated by mass percentage, the hydrophilic frit comprises the following raw materials: 8-12% lithium carbonate, 30-50% calcined talc, 4-8% zinc oxide, 25-35% aluminum oxide, 6-12% quartz and 3-7% silicon carbide; B. Prepare a hydrophilic self-cleaning glaze; wherein, calculated by weight percentage, the hydrophilic self-cleaning glaze comprises the following raw materials: 85-95% of hydrophilic frit, 4-12% of kaolin and 1-3% of silicon carbide; C. Applying the hydrophilic self-cleaning glaze to the body with the concave-convex effect, drying and calcining to obtain the hydrophilic self-cleaning antique brick.

2. The method for preparing a hydrophilic self-cleaning antique tile according to claim 1, characterized in that: In step A and step B, the particle size of the silicon carbide is ≤2 μm; In step A, the particle size of the aluminum oxide is ≤2 μm.

3. The method for preparing a hydrophilic self-cleaning antique tile according to claim 1, characterized in that: In step A, the preparation step of the hydrophilic frit is specifically as follows: mixing the raw materials of the hydrophilic frit evenly according to a ratio, calcining and then quenching with water to obtain the hydrophilic frit; The calcination curve of the hydrophilic frit is: heating from room temperature to 1530° C. at a heating rate of 8 to 10° C. / min, and then keeping the temperature for 35 to 45 minutes.

4. The method for preparing a hydrophilic self-cleaning antique tile according to claim 1, characterized in that: In step A, the hydrophilic frit includes the following raw materials calculated by mass percentage: 10% lithium carbonate, 40% calcined talc, 5% zinc oxide, 30% aluminum oxide, 9% quartz and 6% silicon carbide.

5. The method for preparing a hydrophilic self-cleaning antique tile according to claim 1, characterized in that: In step B, the specific gravity of the hydrophilic self-cleaning glaze is 1.25-1.

45.

6. The method for preparing a hydrophilic self-cleaning antique tile according to claim 1, characterized in that: In step B, the residue of the hydrophilic self-cleaning glaze passing through a 325-mesh sieve is 0.2-0.4% by mass.

7. The method for preparing a hydrophilic self-cleaning antique tile according to claim 1, characterized in that: In step B, the preparation steps of the hydrophilic self-cleaning glaze are: after the raw materials of the hydrophilic self-cleaning glaze are uniformly mixed according to the proportion, sodium carboxymethyl cellulose, sodium tripolyphosphate and water are added for ball milling, and the hydrophilic self-cleaning glaze is obtained by sieving.

8. The method for preparing a hydrophilic self-cleaning antique tile according to claim 1, characterized in that: In step C, the glazing thickness of the hydrophilic self-cleaning glaze is 0.05-0.1 mm.

9. The method for preparing a hydrophilic self-cleaning antique tile according to claim 1, characterized in that: In step C, the calcination temperature is 1200-1220°C.

10. A hydrophilic self-cleaning antique brick, characterized by: The hydrophilic self-cleaning antique brick is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of moon white glaze of Yaozhou Kiln under oxidization atmosphere

    CN103864462A

  • Easy-to-clean daily procelain ware and preparation method thereof

    CN106882961A

  • Self-cleaning glaze and application thereof

    CN115286249A

  • Furnace transmutation purplish red glaze

    CN117023988A

  • Easy-to-clean antique glaze, preparation method thereof and easy-to-clean antique ceramic tile

    CN117125896A